PERAN DIRRECÇÃO TRANSPORTE TERRESTE DALAM MELAKSANAKAN PELAYANAN PUBLIK DOKUMEN KENDARAAN BERMOTOR DI KOTA MADYA BAUCAU, TIMOR LESTE - Roberto da Cruz; José Agostinho da Costa Belo Pereira; Elly Kristiani Purwendah; Seguito Monteiro (Ganesha Law Review, 2024)
Public service is a process of helping other people in certain ways that require sensitivity and interpersonal relationships to create satisfaction and success. Services produce products, both in the form of goods and services. Public services have three important elements, namely, the service provider organization, the service recipient, namely the community and interested organizations, and the satisfaction received by the service recipient. An empirical juridical approach (non-doctrinal) method with secondary data is used to understand ideal public services, while primary data in the form of observations is needed to see how public services are carried out by the Direccão Transporte é Terrestes Municipal of Baucau Municipality. The research results show that the mechanism for providing motorized vehicle documents to the public consists of processing driving licenses and vehicle registration certificates. The obstacles faced by the Direccão Transporte é Terrestes Municipal Apparatus are the lack of human resources, office facilities, transportation, and human resources. The community as the recipient of services has not been provided with good services. The implementation of services by the Direccão Transporte é Terrestes Municipal apparatus is still not timely, responsive, and informative for the people receiving the services